Precipitation and dissolution behaviors of δ phase inside a deformed nickel-based superalloy during annealing treatment - Chen, Ming-Song; Wang, Guan-Qiang; Li, Hong-Bin; Lin, Y. C.; Zou, Zong-Huai; Ma, Yan-Yong; He, Dao-Guang; Zeng, Wei-Dong (Applied physics. A, Materials science & processing, 2019)
The precipitation and dissolution behaviors of δ phase inside a deformed nickel-based superalloy during annealing treatment are investigated. A new method for quantitatively evaluating the content of δ phase was proposed based on SEM micrograph, which was verified by X-ray diffraction (XRD) analysis. The effects of recrystallization during pre-annealing at 980 °C on the precipitation and dissolution behaviors of δ phase in the subsequent annealing treatment at 900 °C and 980 °C are discussed. Moreover, the improved precipitation and dissolution kinetics models are proposed to consider the effects of recrystallization fraction. The results show that: (1) for the precipitation of δ phase at 900 °C, δ phases precipitate first in grain boundaries and then within grains after a long incubation period. Moreover, the interval between adjacent δ phases increases first and then drops with the increasing recrystallization fraction during pre-annealing treatment. A balance between the precipitation and solution of δ phase at the aging temperature of 900 °C can be reached when the holding time is about 12 h; (2) for the dissolution of δ phase at 980 °C, the dissolution equilibrium can be obtained at approximate 200 min. Moreover, more rod-like δ phases can be remained with the increasing recrystallization fraction in pre-annealing treatment.